Mawarung: A Cross-Cultural Communication Bridge in Preserving the Banjar Language - Rafi, Muhammad; Rizqi, Alya Nur; Yanti, Yanti (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study explores how the Mawarung culture serves as a cross-cultural communication bridge in preserving the Banjar language in South Kalimantan. Using observation methods and in-depth interviews with six informants from different ethnic groups, the research found that social interaction in warungs (small food stalls) facilitates language exchange and cultural understanding. The Banjar people, known for their friendliness and initiative, naturally help migrants understand nuances of the Banjar language, such as the differences between ulun and unda.Originally dominated by the older generation, the Mawarung culture is now also adopted by younger people and migrants, making it a space for learning the diversity of Banjar Kuala and Banjar Hulu dialects. Warung owners also contribute by teaching Banjar vocabulary through the naming of food menu items. This phenomenon is evident in the growing number of non-Banjar newcomers who are now fluent in the Banjar language, affirming that Mawarung is not just a place to eat but also a space for preserving language and culture.